Mixed reality in surgical mechatronics: Innovations and challenges in bioengineering education and clinical practice: Realidad mixta en mecatrónica quirúrgica: Innovaciones y retos en la educación en bioingeniería y práctica clínica - Nacarino, Adrian (2024)
Background: Mixed reality (MR), a combination of augmented reality (AR) and virtual reality (VR), has emerged as a key tool in surgical mechatronics, improving precision and visualization in clinical procedures. Methods: This study presents a literature review of recent MR advances from the Scopus database, taking into account its impact on surgery and medical education. Technologies such as Microsoft HoloLens and Magic Leap, as well as neurosurgery and orthopedic simulators, are reviewed. Results: MR enhances surgical precision and reduces operating times, with an average decrease from 121.34 to 97.62 minutes. Despite its potential, challenges include discomfort from prolonged device use and low battery autonomy. Conclusions: MR has the potential to transform surgery and medical education; however, its widespread adoption will depend on overcoming technological and financial barriers, especially in Latin America, where infrastructure is still limited.